Transforming the untransformable:application of direct transformation to manipulate genetically Staphylococcus aureus and Staphylococcus epidermidis - FOSTER, TIMOTHY (My University, 2012)
The strong restriction barrier present in Staphylococcus aureus and Staphylococcus epidermidis has limited functional genomic analysis to a small subset of strains that are amenable to genetic manipulation. Recently, a conserved type IV restriction system termed SauUSI (which specifically recognizes cytosine methylated DNA) was identified as the major barrier to transformation with foreign DNA. Here we have independently corroborated these findings in a widely used laboratory strain of S. aureus. Additionally, we have constructed a DNA cytosine methyltransferase mutant in the high-efficiency Escherichia coli cloning strain DH10B (called DC10B). Plasmids isolated from DC10B can be directly transformed into clinical isolates of S. aureus and S. epidermidis. We also show that the loss of restriction (both type I and IV) in an S. aureus USA300 strain does not have an impact on virulence. Circumventing the SauUSI restriction barrier, combined with an improved deletion and transformation protocol, has allowed the genetic manipulation of previously untransformable strains of these important opportunistic pathogens. Importance: Staphylococcal infections place a huge burden on the health care sector due both to their severity and also to the economic impact of treating the infections because of prolonged hospitalization. To improve the understanding of Staphylococcus aureus and Staphylococcus epidermidis infections, we have developed a series of improved techniques that allow the genetic manipulation of strains that were previously refractory to transformation. These developments will speed up the process of mutant construction and increase our understanding of these species as a whole, rather than just a small subset of strains that could previously be manipulated.